Calculation of the lowest electronic excitations of the alkaline earth metals using the relativistic polarization propagator - Brandt, Sven; Pernpointner, Markus (Chemical physics, 2015)
In this work we use the recently implemented four-component polarization propagator for accurate single excitation calculations of alkaline earth metals and compare our results to experimental data. Various approximations to the Dirac-Coulomb Hamiltonian are additionally tested. In Ca spin-orbit coupling already leads to noticeable zero field splitting, which gradually increases for the heavier homologs finally invalidating the singlet and triplet state characterizations. For all systems we observe a very good agreement with experimental transition energies in the considered energy range. For Sr, Ba and Ra non-relativistic approaches already exhibit unacceptable deviations in the reproduction of transition energies and spectral structure. The obtained excited final states are analyzed in terms of atomic donor and acceptor orbital contributions. Our results stress the necessity to use relativistic implementations of the polarization propagator for an accurate description of both electron correlation and relativistic effects contributing to excitation spectra of heavy systems.